Factors affecting career development of Mara Universiti of Technology lecturers at Samarahan Campus - Chin, Sem Jin (2001)
Strategic interventions are required to keep talented and highly qualified lecturers to serve in UITM in order to gain competitive advantage in the educational world. Many factors affect and contribute to lecturers’ motivation, satisfaction and their career development. This study makes use of survey methodology which aims to discover factors that have significant influence on lecturers’ perception towards career development in UITM.